Potential value of the current mental health monitoring of children in state care in England. Issue 6 (November 2018) - Cocker, Christine; Minnis, Helen; Sweeting, Helen
Abstract : Background: Routine screening to identify mental health problems in English looked-after children has been conducted since 2009 using the Strengths and Difficulties Questionnaire (SDQ). Aims: To investigate the degree to which data collection achieves screening aims (identifying scale of problem, having an impact on mental health) and the potential analytic value of the data set. Method: Department for Education data (2009–2017) were used to examine: aggregate, population-level trends in SDQ scores in 4/5- to 16/17-year-olds; representativeness of the SDQ sample; attrition in this sample. Results: Mean SDQ scores (around 50% 'abnormal' or 'borderline') were stable over 9 years. Levels of missing data were high (25–30%), as was attrition (28% retained for 4 years). Cross-sectional SDQ samples were not representative and longitudinal samples were biased. Conclusions: Mental health screening appears justified and the data set has research potential, but the English screening programme falls short because of missing data and inadequate referral routes for those with difficulties. Declaration of interest: None.